Druhá půlka pravdy: Opominutá dimenze víry vojvodovských Čechů - Jakoubek, Marek (Lidé města, 2010)
This article deals with the religiosity of the Czech Vojvodovo community. The article centres on the recapitulation of the “religious history” of Vovodovan Czechs, starting with the departure of the forefathers of the group from the Czech lands, through the period spent in the Banatian Czech village Svatá Helena, their subsequent arrival in Bulgaria at the end of the nineteenth century, and final their remigration of the community to Czechoslovakia after the Second World War. The last part of the text deals with the existential dimension of Vojvodovan faith. Though fundamental for Vojvodovo Czechs, this dimension has been almost completely omitted by the authors writing on the issue who, instead, preferred the practical aspects of the piety of the community.